2012
DOI: 10.1371/journal.ppat.1002938
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Induced Type VI Secretion System Is Regulated by ExoR-ChvG/ChvI Signaling Cascade in Agrobacterium tumefaciens

Abstract: The type VI secretion system (T6SS) is a widespread, versatile protein secretion system in pathogenic Proteobacteria. Several T6SSs are tightly regulated by various regulatory systems at multiple levels. However, the signals and/or regulatory mechanisms of many T6SSs remain unexplored. Here, we report on an acid-induced regulatory mechanism activating T6SS in Agrobacterium tumefaciens, a plant pathogenic bacterium causing crown gall disease in a wide range of plants. We monitored the secretion of the T6SS hall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(134 citation statements)
references
References 84 publications
9
125
0
Order By: Relevance
“…These include 16 exo genes, responsible for succinoglycan (SCG) biosynthesis (higher expression in ⌬exoR mutants), 51 annotated-and 10 unannotated-motility and chemotaxis genes (lower expression in ⌬exoR mutants), and 22 imp or hcp genes, associated with the type VI secretion system (overexpressed in ⌬exoR mutants). These trends agree with the established hypermucoid and nonmotile phenotypes of ⌬exoR mutants (7,17,18,44) and with the role that ExoR plays in regulating the T6SS presented by Wu et al (22). Noticeably absent from the motility gene category are the class I flagellar synthesis regulators visN, visR (class Ia), and rem (class Ib).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These include 16 exo genes, responsible for succinoglycan (SCG) biosynthesis (higher expression in ⌬exoR mutants), 51 annotated-and 10 unannotated-motility and chemotaxis genes (lower expression in ⌬exoR mutants), and 22 imp or hcp genes, associated with the type VI secretion system (overexpressed in ⌬exoR mutants). These trends agree with the established hypermucoid and nonmotile phenotypes of ⌬exoR mutants (7,17,18,44) and with the role that ExoR plays in regulating the T6SS presented by Wu et al (22). Noticeably absent from the motility gene category are the class I flagellar synthesis regulators visN, visR (class Ia), and rem (class Ib).…”
Section: Resultssupporting
confidence: 89%
“…ChvG-ChvI becomes active under low-pH conditions to elicit their cellular responses. ExoR represses ChvG under neutral conditions, but when A. tumefaciens cells encounter acid, ExoR is proteolyzed to allow the two-component system to become active (21,22). Known targets of regulation by ChvG-ChvI include motility and chemotaxis genes, SCG biosynthesis genes, a type VI secretion system (T6SS), and various virulence genes (22,23).…”
mentioning
confidence: 99%
“…The unmarked genome should help reduce public concerns about the potential toxicity of the current GM crops because of whole T-DNA integration. Apart from T4SS, A. tumefaciens possesses the T6SS which carries antibacterial activity for interbacterial competition; its secretion activity was shown to be suppressed when virulence proteins including T4SS were massively expressed (Wu et al, 2012). Some bacterial T6SS effectors are able to manipulate host immunity in animal systems, but there is no solid evidence to suggest that A. tumefaciens or other plant pathogens can use their T6SS effectors to manipulate host immunity in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the affinity of the ChvE protein for sugar acids is increased at low pH, suggesting a link between the sugar and acidity response in A. tumefaciens (Hu et al, 2012). A. tumefaciens utilizes the ChvG/ChvI two-component system to activate the transcription of virG and induces expression of several other bacterial genes (Mantis and Winans, 1992;Chang and Winans, 1996), including genes involved in chemotaxis and motility, several chromosome-encoded virulence genes, succinoglycan biosynthesis genes, and the gene cluster encoding the type VI secretion system (T6SS) (Yuan et al, 2007a;Wu et al, 2008;Wu et al, 2012). Recent studies further identified ExoR as a periplasmic negative regulator acting upstream of the ChvG sensor kinase to repress acid-inducible gene expression (Wu et al, 2012;Heckel et al, 2014) and uncovered a role for the T6SS in interbacterial competition activity during the plant colonization process (Ma et al, 2014).…”
Section: Sensing and Regulation Of Virulence Genes Of A Tumefaciens mentioning
confidence: 99%
“…Agrobacterium tumefaceins C58 harbors one T6SS that is activated transcriptionally by an ExoR-ChvG/ChvI signaling cascade and posttranslationally via threonine phosphorylation when sensing acidity (34)(35)(36). Three type VI effectors, namely type VI amidase effector (Tae) and type VI DNase effectors (Tde1 and Tde2), confer antibacterial activity of this bacterium.…”
Section: Significancementioning
confidence: 99%